Editorial statement: Lessons from Goodhart's law for the management of the journal - Diego Varela; Giacomo Benedetto; Jose Manuel Sanchez-Santos (European Journal of Government and Economics (EJGE), 2014)
In this editorial statement we summarise some of the discussions we have had in the last months regarding the risks associated with the use of indicators for the measurement of research outputs, and how these risks should affect the management of the European Journal of Government and Economics. In particular, we focus on the consequences of the so-called Goodhart's law, which states that when a measure becomes a target, it ceases to be a good measure. We also explain the latest developments in the journal in the light of our previous editorial statements, and present our strategy for the upcoming years.
Keywords: 330; academic publishing; academic journal; Goodhart's law; indicators; research assessment